2005
DOI: 10.1007/s00335-005-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of human gastric cancer

Abstract: To elucidate the genetic events associated with gastric cancer, 124,704 cDNA clones were collected from 37 human gastric cDNA libraries, including 20 full-length enriched cDNA libraries of gastric cancer cell lines and tissues from Korean patients. An analysis of the collected ESTs revealed that 97,930 high-quality ESTs coalesced into 13,001 clusters, of which 11,135 clusters (85.6%) were annotated to known ESTs. The analysis of the full-length cDNAs also revealed that 4862 clusters (51.7%) contained at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…To better understand the relationship between G clusters and GTP-binding activity, we characterized the sequence requirements of one of these aptamers, clone 4–56, in greater detail. This aptamer was chosen for initial characterization efforts because ( i ) it is known to be expressed (as part of a 486-nucleotide transcript of unknown function) (Oh et al, 2005); ( ii ) pilot experiments revealed that its GTP-binding activity is conserved in primates (Figure S1), consistent with a possible biological role; and ( iii ) it is small (40 nts), which we anticipated would simplify its minimization.…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the relationship between G clusters and GTP-binding activity, we characterized the sequence requirements of one of these aptamers, clone 4–56, in greater detail. This aptamer was chosen for initial characterization efforts because ( i ) it is known to be expressed (as part of a 486-nucleotide transcript of unknown function) (Oh et al, 2005); ( ii ) pilot experiments revealed that its GTP-binding activity is conserved in primates (Figure S1), consistent with a possible biological role; and ( iii ) it is small (40 nts), which we anticipated would simplify its minimization.…”
Section: Resultsmentioning
confidence: 99%
“…KsgA orthologs from non-bacterial sources are represented by Dim1 from Saccharomyces cerevisiae (Sc-Dim1) (Lafontaine et al, 1995; Lafontaine et al, 1998) and from human (Hs-Dim1) (Law et al, 1998; Oh et al, 2005), Pfc1 from Arabidopsis thaliana (Tokuhisa et al, 1998) and mitochondria mtTFB from human (Hs-mtTFB) (Cotney and Shadel, 2006; McCulloch et al, 2002; Seidel-Rogol et al, 2003). The mtTFB from yeast (Sc-mtTFB), however, has lost its MTase activity (Klootwijk et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…TOPBP1 (topoisomerase DNA II-binding protein 1) represents a very interesting candidate for CRC genetic susceptibility as it contains multiple BRCT domains, the C-terminal portion of the BRCA-1 gene, and it has a critical role in the control of DNA damage and replication checkpoint (Gong et al , 2010). On the other hand, CDV3 (carnitine deficiency-associated gene expressed in ventricle 3), also known as H41 , seems to be involved in cell proliferation and altered in gastric cancer (Oh et al , 2005). It is noteworthy that the TOPBP1 and CDV3 genes lie next to each other in 3q22 and rs1444601 and rs13088006 are only 34 kb apart.…”
Section: Discussionmentioning
confidence: 99%